Post‐polymerization surface segregation in thin PECVD siloxane films leading to a self‐regenerative effect. Issue 9 (28th March 2017) - Zuber, Kamil; Markanday, Jonathon F.S.; Hall, Colin; Evans, Drew; Charrault, Eric; Murphy, Peter
Abstract : In this work, the post‐synthesis changes of chemistry and surface properties of the siloxane coatings synthesized via Plasma Enhanced Chemical Vapor Deposition (PECVD) are investigated. The study shows that in contrast to the volume of the siloxane coating, which undergoes oxidation and increase in crosslinking density during several days after deposition, the surface of the coating displays different effects. Further analysis shows that this is the result of short polymer fragments diffusing onto the surface, affecting wettability of the surface and adhesion. It has also been observed that these short polymer fragment may be removed and will in time replenish, giving the coatings a regenerative nature. Abstract : In this work, the post‐synthesis changes of chemistry and surface properties of the siloxane coatings synthesized via Plasma Enhanced Chemical Vapor Deposition (PECVD) are investigated. The study shows that in contrast to the volume of the siloxane coating, which undergoes oxidation and increase in crosslinking density during several days after deposition, the surface of the coating displays different effects. Further analysis shows that this is the result of short polymer fragments diffusing onto the surface, affecting wettability of the surface and adhesion. It has also been observed that these short polymer fragment may be removed and will in time replenish, giving the coatings a regenerative nature.